Raising environmental awareness through community-based efforts to clean and preserve the Karang Mumus river, Samarinda City - Intan Kinanthi Damarin Tyas; Devy Indah Paramitha; Jeane Betty Kurnia Jusuf (Universitas Muhammadiyah Magelang, 2024)
River pollution, particularly from littering, has long plagued Samarinda City. The Karang Mumus River exemplifies this challenge, with heavy downstream debris and a lack of upstream catchment areas leading to seasonal flooding. This pollution significantly reduces the community's quality of life and hinders sustainable development efforts. To address this, a community service program was initiated to raise environmental awareness through cleaning and maintaining the Karang Mumus River. The program utilized outreach methods to educate the